Sri Sumarah Karya Umar Kayam “Tinjauan Hegemoni Kultural” - Insum Malawat (Balai Bahasa Provinsi Papua, 2019)
Hegemony is not the domination context by using the dominance, but the convention accompany leaders. In economy activity mission, Gramsci mention three parts. The first parts might be created economics collective aware in certain social unit. The second part is the part that the members from a class unit get solidarity aware on it, but still on economics environment naturally. The third part is somebody becomes aware that his interest corporate in present and future developing block the corporations limits from natural economics class, but raising on the other subordinates groups. This momen namely being hegemony which the leadership of fundamental group for subordinate groups on economics activity context.On cultural level, Gramsci devides the hegemony into three culture forms, it is the hegemonic culture, settle culture, and come on up cultura. Hegemonic culture is the culture that hand up the leader on idea about culture commonly as a unity. The settle culture is past culture that struggle to depend their live. And the come up culture is the culture that lives on struggle to get and create hegemony. Based that phenomenon, Sri Sumarah story by Umar Kayam is a literary work that implicate to hegemony of Javanese culture.